Factors of audit committee independence: An empirical study from an emerging economy - Md. Hossain Ali (Taylor & Francis Group, 2021)
This study aims to examine the factors affecting the independence of audit committees (ACs) in the nonfinancial sector of Bangladesh. It is a quantitative study on 109 Dhaka Stock Exchange (DSE) listed nonfinancial firms from the year 2013 to 2017 producing 502 firm-year observations. Pooled OLS, random effect, Logit, Tobit, and lag model regressions are the statistical tools applied to test the hypotheses of this study. Empirical results show that large corporate boards and more independent directors on corporate boards provide more independence to the audit committees while large audit committees lag behind regarding independence. It is also found that audit committees enjoy more independence in firms having more institutional ownership but less independence in firms having more insiders’ ownership. The regulation plays an important role by commanding the size and independence of boards which in turn significantly affect audit committee independence. Further regulatory reforms may, therefore, be considered to ensure more independence of corporate audit committees.